THE PROBLEMS OF DEVELOPING NEW BEACHES FOR TOURISM OBJECTS IN BANTUL: A CASE STUDY OF PANTAI GOA CEMARA AND PANTAI BARU - , NURUL FARKHIATUN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pantai Goa Cemara and Pantai Baru are the new beaches in Bantul. Culture and Tourism Department and Pokdarwis has programs to improve development tourism objects in Bantul, improvement program in 2013 are: promotion, tourism attraction, facility, and pokdarwis. Culture and Tourism Department of Bantul and also the Pokdarwis of the two beaches have important roles in their development as tourism sites. Those parties face some problems in increasing the potentials of both beaches. Therefore, this graduating paper aims to know the problems faced by Culture and Tourism Department and Pokdarwis, as well as to suggest solutions to the problems. To collect the data for the research, the writer gathers data from some files available at the office of Culture and Tourism Department and also reads books and article from internet to get information about tourism development. In addition, the writer observes the conditions of Pantai Goa Cemara and Pantai Baru and interviews the tourists. The writer also do interview with staffs of Culture and Tourism Department to get information about their program have done and the solution to solution, and invirvew with both Pokdarwis to get information about the problem, also interview with some visitors to know the problems faced both beaches and know the condition of both beaches. The problems of developing Pantai Goa Cemara and Pantai Baru are: lack of security, cleanliness, parking area, human resources, culinary and entertainment. Culture and Tourism Department also Pokdarwis have solutions to the problems by strengthening the security, cooperting with other parties to finance the development, training the pokdarwis members and providing sanitary equipment.